Blog Design Solutions - Rutter, Richard; Budd, Andy; Collison, Simon; Davis, Chris J.; Heilemann, Michael; Sherry, Phil; Powers, David; Oxton, John (Apress : Imprint: Apress, 2006)
Blogging has moved rapidly from being a craze to become a core feature of the Internet-from individuals sharing their thoughts with the world via online diaries, through fans talking about their favorite sports teams or music, right up to serious business minds discussing industry futures. And that includes you, right? If you haven't got a blog already, you want to start one, and want to find out how. If you have already got one, you want to know how to customize it, and make it look cooler than everybody elses. In either case, this is the ideal book for you. In this book, a team of renowned web designers take you through the ins and outs of putting together great blogs. They waste no time harking on about the philosophy of blogs, or the community behind them. Instead, they get straight to the practical details, showing how to set up a basic blog in some of the world's most popular blogging engines Movable Type, ExpressionEngine, WordPress, and Textpattern. With your blog set up, they then show you how to build great looking, usable layouts for your blog. The last chapter even shows you how to build your very own PHP/MySQL-based blog engine! With this book in hand, you'll have found your way to blog heaven in no time!